(untitled) (Homoeopathy for All, 2022)
Hidradenitis suppurative (HS), also known as Verneuil’s disease or acne inversa, and occasionally is spelled hidradenitis, is a chronic, recurrent, debilitating disease that presents with painful, inflamed lesions in the apocrine-gland–bearing areas of the body, most commonly the axillary, inguinal, and anogenital. Although the name "hidradenitis suppurativa" implies a suppurative disorder that primarily involves sweat glands, increasing knowledge of the pathogenesis of the condition has led to the prevailing theory that HS is a chronic follicular occlusive disease involving the follicular portion of folliculopilosebaceous units.